The Role of the Use aljazeera.net Website in Improving the Mastery of Modern Arabic vocabulary in Learning the Tarjamah Lishahafah Majoring in Arabic Education State Islamic Institute of Kediri - Sholihuddin, Ahmad; Muslimah, Maziyyatul; Riyani, Adina (Program Studi Pendidikan Bahasa Arab, Fakultas Tarbiyah, IAIN Kediri, 2023)
The use of media is very important in learning, including learning Arabic. Media is an important element. Media is very helpful for teachers to maximize the delivery of material to students. Media can also be the main source of learning and as a support for learning. There are various kinds of learning media, one of which is website-based media. In learning to translate lishahafah PBA IAIN Kediri using website-based learning media, namely aljazeera.net as the main source of learning. This study aims to (1) describe the use of the aljazeera.net website media in learning to translate lishahfah PBA IAIN Kediri, (2) describe the role of the aljazeera.net website media in improving modern Arabic vocabulary mastery in learning translation of lishahfah PBA IAIN Kediri. To achieve this goal, the researcher used a descriptive qualitative approach. Data collection techniques used interviews and questionnaires with triangulation techniques to test the validity of the data. Data analysis uses the Miles and Huberman model, namely, data reduction, data presentation and conclusions. The results showed that 1) the use of the media website aljazeera.net was used in learning to translate lishahafah because on the website there were various Arabic news stories. The use of the aljazeera.net website as a learning medium is done by students searching for news texts then translating the news and then presenting the results of their translations. Although there are obstacles in using the website 2) the media website aljazeera.net contributes to making learning more effective and efficient, increasing knowledge about new terms in Arabic, knowing how to write the correct word and sentence tarkib, improving translation skills and adding insight .